Peran Media Digital Sebagai Pemain Kunci Penentu Arah Demokrasi di Indonesia Tahun 2023 - Ahdarrijal, Yujitia; Rahmawati, Dian Eka (Universitas Negeri Surabaya, 2024)
This study aims to see the role of digital media in determining the direction of democracy and public opinion. This research uses a descriptive qualitative method with case studies in Indonesia and unit analysis using Nvivo 12 Plus software, which is analyzed with Computer Assistant Qualitative Data Analysis (CAQDS) and crosstab. The urgency of the media as an essential actor in democracy is because it can present broad information, active participation, responsiveness, and diversification of perspectives that shape public opinion. The results of this study show that there are three important points. 1) Digital media is able to create spaces for democratic actors in various sectors then, 2) Digital media is an informative and participatory domain, and the last is 3) Digital media is a supervisor of democracy in Indonesia; criticism suggestions and evaluations are straightforward to do by several actors in it. The media is responsible for ensuring the continuity of a healthy democracy. We need cooperation among governments, the private sector, and civil society to support democratic values in media. Criticism, literacy, and active public participation on social media are crucial for maintaining democracy in the digital era.